Reactive oxygen species may unite many mechanisms by which calcium oxalate stones form - Chi, Thomas; Taylor, Eric; Stoller, Marshall L. (Translational Andrology and Urology, 2014)
The pathogenesis of calcium oxalate nephrolithiasis remains a mystery, but the suggestion that it is simply due to perturbations in urinary super saturations remains an inadequate explanation (1). It is likely due to much more complex and nuanced mechanisms that incorporate inorganic and organic components. How these components propagate into Randall plaques or calculi or even where these stone-forming events occur (vasa recta, collecting ducts, or the basement membrane of the loops of Henle) is debatable. Metabolic derangements leading to uncontrolled reactive oxygen species (ROS) generation or a reduced antioxidant capacity to alleviate oxidative stresses may play a role in Randall plaque formation through tissue damage and/or ROS-induced altered gene expression.